STRATEGI PENGEMBANGAN TERNAK KAMBING LAKOR: PENDEKATAN PRODUKSI, PENDAPATAN, DAN ANALISIS SWOT - Erick W. Talakua; Leonard O. Kakisina; Natelda R. Timisela (JSEP (Journal of Social and Agricultural Economics), 2022)
This study aims to analyze the factors that influence the production and income of Lakor goats. The research used a survey method using interview techniques and field observations. The study was conducted in Letoda Village, Lakor Island District, Southwest Maluku Regency, with the number of respondents selected as many as 45 people (50%) from 90 population of Lakor goat breeders. Primary and secondary data were analyzed using qualitative and quantitative descriptive methods. The results showed that determining the factors that affect the production of Lakor goats after being analyzed by multiple regression analysis showed that the independent variables, namely length of business, seeds, number of workers, area of ​​cages, and feed together, significantly affected the production of Lakor goats. Meanwhile, for the effect of each independent variable on the production of Lakor goats, it was found that the length of business, seeds, cage area, feed had a significant effect, and labor had no effect on the production of Lakor goats. The income of the Lakor goat breeder per year is IDR 10,963,611. The feasibility of the Lakor goat livestock business has an R/C ratio value of 2.03 and a B/C ratio of 1.03 so that the Lakor goat business is feasible to be cultivated and developed for the welfare of the community.